PENGEMBANGAN PENDEKATAN OPEN ENDED DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SEKOLAH DASAR DI KALIMANTAN UTARA - Ahsan Sofyan; Disman Disman; Kokom K; Erlina W (Universitas Borneo Tarakan, 2019)
The application of the Open-ended approach in the social studies learning process can develop high-level thinking skills of elementary school students. The formulation of the problem in this study is how to develop, implement and influence and impact the application of the Open-Ended learning model in social studies learning to improvethe high-level thinking skills of elementary school students. The method used is the research and development (R D) of Borg and Gall. The research locations were ten elementary schools in five districts/cities in North Kalimantan. The subjects of this study were high-class teachers and students (grades 4.5, and 6) using purposive sampling techniques. The results showed that the Open Ended learning model was feasible to use based on peer evaluations, expert lecturers, and effective teachers could improve the high-level thinking skills of students in Elementary School seen from the application of the Open-Ended learning model in the learning process when the experiment class students were more higher than control class students. In the final model validation test, where the average experimental class post-test was 83.33 higher than the control class, which obtained an average of 80.07.